A Comparative Analysis of the Functions of the Preverbal Markers 'Bin' and 'Go' in Jamaican Post-Creole and Hawaiian English - Dr. Moslih Aowni Saeid (المجلة الدولية للعلوم الإنسانية والاجتماعية)
Pidgin and Creole languages are probably not recent innovations in human linguistic history. It is likely that ancient Egyptian, Sumerian, and Chinese soldiers and merchants used variations of Pidgin to communicate with the so-called "barbarians" they encountered at the borders of their empires. Hall (1966:3)